Evaluasi Pelaksanaan Supervisi dengan Menggunakan Metode Coaching di RSIA Bunda Denpasar - Prihandhani, IGAA Sherlyna; Widiastuti, Putu; Trisna, Made Oktaviani Bulan (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
Background: Hospitals are a key pillar of the healthcare system, providing complex services to improve public health. Nursing care is an essential part of hospital function, aiming to maintain optimal public health. Nursing care is a professional service focused on individuals, families, groups, and communities, both in health and illness. Purpose: evaluation efforts for the implementation of supervision using the coaching method at Bunda Denpasar Women's and Children's Hospital.. Method: The training method will be conducted face-to-face for one month in four sessions. The sessions consist of a pre-test assessment, lectures, video screenings, targeted mentoring, and a post-test assessment. Results: Based on the pre-test results, the effectiveness of supervision was 65, and after the coaching intervention, the post-test score was 97. Conclusion: This demonstrates that the use of coaching in supervision improves performance and service delivery. Supervision in the nursing context is the process of monitoring and guidance carried out by direct superiors, such as ward heads, to ensure the implementation of nursing care meets established standards.